Analysis of the effect of Fear of Missing Out (FOMO) and the use of paylater application on impulse buying behavior (review of Maqashid Syariah) - Harahap, Muhammad Ikhsan; Soemitra, Andri; Nawawi, Zuhrinal M (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
This study aims to determine the effect of Fear of Missing out and the use of paylater applications on impulse buying behavior in terms of maqashid sharia. This study uses a quantitative approach using a sample of students from the Faculty of Islamic Economics and Business who use the paylater application. Data analysis using Partial Least Square (PLS). The results of the study stated that Fear of Missing Out and the use of the paylater application had an effect on impulse buying behavior. Based on the maqashid sharia review, the Fear of Missing out phenomenon and the use of paylater applications and impulse buying behavior are not in accordance with sharia goals